The Correlation of Body Mass Index and Physical Activity on Cardiorespiratory Endurance among Elderly - I Kadek Dwi Widhi Dharma; I Putu Prisa Jaya; I Made Dhita Prianthara (Physical Therapy Journal of Indonesia, 2021)
Background: Elderly is assumed as a person who has been at the age of 60 and will be some alterations, physical alteration in term ages. The physical alteration that is commonly found in the elderly is a condition of the body mass index that will not be taken care of optimally due to the degenerative factor. Purpose: This study is aimed at proving the relation of body mass index towards the cardiorespiratory endurance along with the relation of physical activities towards the cardiorespiratory endurance. Methods: The study design was cross sectional with the population of the elderly in Banjar Alas Arum in which they qualified the inclusion and exclusion criteria. From the elderly that had been selected by means of purposive sampling, it was obtained 48 samples. The BMI was measured by formula calculation. The physical activity level was measured by the International Physical Activity Questionnaire and the cardiorespiratory endurance used 6 minutes walking test. The data were analyzed by software computer which was Somers’ D test. Results: The result of this study showed that by 48 the relation of BMI towards the cardiorespiratory endurance showed that the result of p was 0.000 (p<0.05). Concerning on the relation of physical activities towards the cardiorespiratory endurance shown that the result of p was 0.000 (p<0.05). Conclusion: It can be concluded that there is a significant relation in this study.